2009
DOI: 10.1515/cclm.2009.288
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to mutated citrullinated vimentin and antibodies to cyclic citrullinated peptides in juvenile idiopathic arthritis

Abstract: Background: The goal of the study was to assess the presence of antibodies to mutated citrullinated vimentin (anti-MCV) and cyclic citrullinated peptides (anti-CCP) in patients with juvenile idiopathic arthritis (JIA) compared with patients with other juvenile onset rheumatic diseases. Methods: The study included 56 patients who fulfilled the International League of Associations for Rheumatology (ILAR) classification criteria for JIA, and 17 control patients with other juvenile onset rheumatic diseases. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Occurrence of autoantibodies was rare in our study, much like in the majority of previous studies on JIA [9,21-23]. As in adult RA, occurrence of IgM RF in JIA has been shown to correlate with joint damage or joint space narrowing [5,17,22,24-26].…”
Section: Discussionsupporting
confidence: 82%
“…Occurrence of autoantibodies was rare in our study, much like in the majority of previous studies on JIA [9,21-23]. As in adult RA, occurrence of IgM RF in JIA has been shown to correlate with joint damage or joint space narrowing [5,17,22,24-26].…”
Section: Discussionsupporting
confidence: 82%
“…Other studies have examined the significance of citrullinated fibrinogen [13-19], citrullinated α-enolase [13,20,21], citC1 III [13,22-24], and citrullinated vimentin [13,25-30] in RA and experimental arthritis. To date, only two studies on citrullinated vimentin has documented the identity and evaluated the significance of citrullinated proteins in a JIA population [31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Citrullinated vimentin has been shown to be the target for the previously described RA-specific Sa antibodies (Vossenaar et al, 2004). The prevalence of anti-MCV has been reported recently to vary between 5.4 and 10.5%, and it was also found in disease controls (Kuna et al, 2009;Morbach et al, 2010;Gilliam et al, 2013). The prevalence of anti-MCV in our JIA patient group was 28.4%, which was higher than that of any other ACPA; however, 3 of the 49 healthy controls were found to be positive for anti-MCV, and 23.6% of disease controls also showed positive reactivity, very similar to the results reported by Kuna.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, each ACPA had a different prevalence among the JIA subtypes, mainly because of the antigens used. Anti-CCP has been extensively studied in JIA, and the sensitivity of anti-CCP has been reported to be between 1.8 and 27.9% (Machado et al, 2005;Brunner and Sitzmann, 2006;Gilliam et al, 2008;Habib et al, 2008;Kuna et al, 2009). In the present study, anti-CCP was identified in 7 (8.9%) of 81 JIA patients, agreeing with the reported rates in most published studies, and the positivity (9.9%) was slightly improved by when anti-CCP3.1 IgG and IgA were used simultaneously to detect CCP.…”
Section: Discussionmentioning
confidence: 99%